Thematic Analysis - Final Roadmap - Moreno Beguerisse, Mariale; Charnley, Fiona; BESSIERE, Dorothée; Tiwari, Ashutosh (Cranfield University, 2017)
Complete thematic analysis to create the roadmap that sets the vision for the UK's consumer goods industry';Complete thematic analysis to create the roadmap that sets the vision for the UK's consumer goods industry
Keywords: re-distributed manufacturing'; 'big data'; 'consumer goods'; 'localisation'; 'customisation'; 'Manufacturing Management'; 'Manufacturing Processes and Technologies (excl. Textiles)'